HEALTH POLICY TOWARDS OBESITY HAS AN IMPACT ON NON-COMMUNICABLE DISEASES (NCDS) OVER THE LAST 10 YEARS: A BIBLIOMETRIC ANALYSIS - Azhari, Salma Widya; Violeta, Dea Tiany; Sitorus, Vetrisia; Tanziha, Ikeu (Media Gizi Indonesia, 2025)
The prevalence of obesity has significantly increased, affecting millions of people worldwide. Obesity is a growing public health concern worldwide. According to the statistical data, millions of individuals were classified as obese. Policy plays a crucial role as a macro-level factor in shaping behavioral changes. This study aimed to analyze global trends in health policy research on obesity and its impact on Non-Communicable Diseases (NCDs) from a bibliometric perspective using Scopus-indexed documents. Data analysis methods and visualization techniques were applied to publications from 2014 to 2023 using the keywords (overweight OR obesity OR obes* OR over$weight) AND (health AND (policy OR regulation OR procedure OR system) AND ncd*). RStudio and VOSviewer were utilized for bibliometric publication statistical analysis, resulting in 132 publications from the Scopus metadata. We used bibliometric analysis to examine the published literature and visualize development trends regarding the effects of health policies on obesity. These findings indicate that health policies related to obesity focus on the mechanisms that affect NCDs. The identified policies included taxes on unhealthy foods and food subsidies. Health policies play a crucial role in preventing obesity and reducing its impact on NCDs. Collaboration between the government and various sectors of society is necessary to implement effective policies for the prevention of obesity. Future policies are expected to be adopted by each country regarding unhealthy food tax policies, food subsidy policies, Early Care and Education (ECE) policies, and Health in All Policies (HiAP).